Software package for studying measuring instruments - Puhanovskyi, Oleh (Perfect Publishing, 2024)
Distance forms of education are becoming more influential in the modern world. The author proposes a variant of virtual learning tools in the field of using measuring instruments. A comparison is made with known software products and the need for work in this direction is justified.
Keywords: virtual devices; distance learning; device emulation; virtual laboratory; VS C#